Urban Heat Islands: Potential effect of organic and structured urban configurations on temperature variations in Dubai, UAE - Taleb, Dana (2011)
Urban heat islands are phenomena that occur coupled with rapid urban developments. The study was carried out to show the effect of organic and structured urban configurations on temperature variations throughout the year, especially in summer. The study carried out investigated a larger area of the city rather than merely building-to-building relationships. It went beyond the confinement of street and building geometries and investigated how a number of these geometries put together in one context contributed to temperature variations. A computer simulation software was used to simulate three different urban configurations, namely the Bastakiyah, Orthogonal, and Volume Ortho configurations in Dubai, UAE. The simulations were carried out for summer, winter, and autumn with initial input temperature value of 305.15K and varying initial wind speeds. Assessment of the results showed that the Bastakiyah configuration recorded lower temperatures in summer than both the Orthogonal and Volume Ortho configurations. The Orthogonal configuration did not respond as an intermediate configuration between the organic and highly structured. The Volume Ortho configuration, though recorded the highest wind values, did not result in lowered temperature values. It was shown that different configurations manipulated the behavior of the wind within the configuration. The sky-view factor and standard deviation were plausible explanations in the absence of obvious trends in some cases, and showed how urban configurations impacted temperature variations. It was concluded that, given this specific site location and the alignment of prevailing winds parallel to the roads, the Bastakiyah configuration showed better potential of the three in terms of temperature performance.